Literasi Istilah Politik pada Kegiatan Peningkatan Keterampilan Tugas Satlinmas dalam Pemilu 2024 di Desa Wadunggetas - Faraba, Karina Sofiananda Armaza; Gunawan, Herri; Alhasbi, Faruq (Politeknik Negeri Samarinda, 2024)
This community service activity aims to provide a literate understanding of political terms in activities to improve the skills of Satlinmas duties in organizing elections. This service is carried out systematically in three stages of activity namely, identifying problems, establishing collaboration with Election Supervisory Agency (BAWASLU) of Central Java Province, Subdistricts, and PPD of Wadunggetas, and conducting literacy training to improve the skills of Satlinmas duties. It is hoped that the socialization of political term literacy will help Satlinmas' understanding in improving their job skills. The activity of introducing literacy to political terms for Wadunggetas Satlinmas members was carried out to increase members' insight in supporting the 2024 election activities. Apart from that, by understanding political terms related to election activities, it is hoped that Satlinmas members will be able to optimize coordination in accordance with the existing organizational structure, as well as collaborate with many parties related to election activities.